Cardiovascular Disease, Comorbidities, and Late Adult in Indonesia: a Cross-Sectional Population-Based National Survey - Tri Wahyuni; Dwi Rahmah Fitriani; Joanggi Wiriatarina Harianto; Ritanti Ritanti (Media Keperawatan Indonesia, 2022)
The aging population is predominantly predisposed to heart illness. Age is an autonomous danger factor for cardiovascular disease (CVD) in adults, but this risk is exacerbated by additional factors, including comorbidities. This study aimed to determine the prevalence of cardiovascular disease and the association between comorbidities and cardiovascular disease among late adults in Indonesia. This cross-sectional research utilizes the data national population survey from the Indonesia Family Life Survey wave 5 (2015). Multistage stratified random sampling was utilized to choose the respondents to respond to a structured questionnaire interview, laboratory test, and anthropometric measurements. Multivariable logistic regression was utilized to determine the association. The result was respondents’ age mean was 48.31 (±5.83) years. CVD prevalence was 2.36% (95% CI: 2.07 – 2.70). The final model of a multivariable analysis using multiple logistic regression indicated that CKD (adj. OR = 3.04, 95%CI 1.76 – 5.24, p = <0.001), hyper cholesterol (adj. OR = 2.77, 95%CI 1.20 – 3.90, p = <0.001), stroke (adj. OR = 2.66, 95%CI 1.36 – 5.24, p = 0.004), having hypertension (adj. OR = 1.83, 95% 1.35 – 2.49, p = <0.001), high blood sugar (adj. OR = 1.82, 95%CI 1.17 – 2.86, p = 0.008), were significantly associated with CVD among late adults. Other significant covariate was age (adj. OR = 1.04, 95%CI 1.01 – 1.06, p = 0.003) and sex (adj. OR = 1.43, 95%CI 1.07 – 1.92, p = 0.015). The conclusion was comorbidities, age, and sex was associated with CVD among late adults in Indonesia.